The Effect of Service Context in Consumer Relationship Proneness and Behavior - Teresa Fernandes (2013)
Objective: The paper discusses the effect of context on service relationships. Considering the customers' point of view, we argue that customers may hold different proneness to establish a relationship with the provider depending on the specific service context. Different relationship proneness will, in turn, influence the more or less favorable behavior of the consumer in the relationship. As such, this paper aims to increase understanding of consumer relationship proneness and its role in different service settings. Methodology: Data were collected in two contexts, high and low contact services (health services and wholesales, respectively). Through a convenience sample of 516 consumers, we conducted a survey to examine differences in consumer proneness and behaviors in both contexts. Conclusion: Results revealed that consumer relationship proneness and behaviors vary significantly among the contexts studied. In the high contact service (healthcare services), customers exhibit higher relationship proneness and show more favorable behaviors towards the relationship, when compared with the low contact service (wholesales). It was also found that the majority of consumer behaviors are, in both contexts, correlated with relationship proneness. Implications: This research aims to fill an existing gap in the RM literature by taking consumer relationship proneness into consideration. Additionally, the effect of service types has not yet been fully explored, particularly in the customer relationship field. In managerial terms, the results of this study provide guidance to managers to differentiate customer relationship strategies according to the specific service context that they operate in.